2021
DOI: 10.1038/s41598-021-90936-7
|View full text |Cite
|
Sign up to set email alerts
|

Portable rotating grating stimulation for anisometropic amblyopia with 6 months training

Abstract: Treatment of grating stimulation has been used in amblyopia for decades, but high dropout rate and inconvenience for daily practice occur in previous studies. We developed a home-based portable system with rotating grating stimulation on a tablet. Thirty anisometropic amblyopic children were randomly allocated into the control or Grating group. They drew contour of the picture under patch of a better eye for 6 months. Best-corrected visual acuity (BCVA), grating acuity (GA), and contrast sensitivity (CS) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The refractive power of the eyes is measured using the equivalent spherical diopters (spherical diopters + 1/2 cylindrical diopters) as the measurement standard. Based on current domestic and foreign literature, this study uses a difference of ≥ 1.00D in equivalent spherical diopters (SE) between the two eyes as a diagnostic criterion [13][14][15]. A three-year study conducted in New Zealand found that the incidence of exotropia increases with myopia, and the degree of esotropia corresponds to hyperopia, with a higher degree of hyperopia associated with a higher probability of esotropia.…”
Section: Near Stereo Vision Titmus Resultsmentioning
confidence: 99%
“…The refractive power of the eyes is measured using the equivalent spherical diopters (spherical diopters + 1/2 cylindrical diopters) as the measurement standard. Based on current domestic and foreign literature, this study uses a difference of ≥ 1.00D in equivalent spherical diopters (SE) between the two eyes as a diagnostic criterion [13][14][15]. A three-year study conducted in New Zealand found that the incidence of exotropia increases with myopia, and the degree of esotropia corresponds to hyperopia, with a higher degree of hyperopia associated with a higher probability of esotropia.…”
Section: Near Stereo Vision Titmus Resultsmentioning
confidence: 99%